Finding the right role for social media in innovation - Roberts, Deborah L.; Piller, Frank (Massachusetts Institute of Technology, Cambridge, MA, 2016)
Although some companies have been able to use social media to develop new insights that lead to successful new products, many others simply do not know how to utilize social media for innovation. Whats more, some companies have seen their innovation performance negatively affected. Nevertheless, social media provides a game-changing opportunity for companies that learn how to exploit it. In order to use social media for innovation, organizations need clear strategies and objectives. The authors of this article recently studied the social media practices of large global companies as they relate to new product development, using data from the Product Development Management Associations 2012 Comparative Performance Assessment Study. Broadly speaking, we found that for many companies, the results of using social media for new product development fell short of expectations. Less than 50% of the companies surveyed use social media during the new product development process. Many of the companies we surveyed didn't seem to recognize the differences and functionalities of different social media platforms and media sources. It is critical that top leadership play an active role by encouraging cooperation and idea sharing among the various players.